IMPACT OF POSTMASTECTOMY RADIATION THERAPY ON IMPLANT-BASED BREAST RECONSTRUCTION OUTCOMES IN BREAST CANCER PATIENTS (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
Breast reconstruction has become an essential component of modern breast cancer management, significantly improving psychosocial well-being and postoperative quality of life. However, the integration of postmastectomy radiation therapy (PMRT) into reconstructive treatment remains clinically challenging due to its association with postoperative complications and compromised aesthetic outcomes. This thesis evaluates the influence of radiation therapy on immediate implant-based breast reconstruction in patients treated for breast cancer. The analysis is based on a retrospective clinical cohort of 132 patients who underwent one-stage reconstruction after mastectomy. The findings indicate that PMRT is strongly associated with an increased incidence of postoperative complications, particularly capsular contracture, while implant-based reconstruction remains a practical and acceptable option for selected patients. The study also highlights the possible protective value of polyurethane implants and additional lower-pole coverage in reducing radiation-related morbidity. These data support a personalized reconstructive strategy that balances oncologic safety, technical feasibility, and long-term quality of life.